Empowering smallholder wheat farmers with NextGen Agroadvisory in Ethiopia: A tailored, season-smart, and scalable approach - Mesfin, Tewodros; Liben, Feyera; Ebrahim, Mohammed; Tesfu, Daniel; Gashaw, Getachew; Bekele, Hawinet; Tilaye, Asmalu; Erkossa, Teklu; Abera, Wuletawu; Ayele, Kebede; Tamene, Lulseged D. (2023)
This technical report presents a comprehensive overview of the pilot initiative for site-specific and season-smart fertilizer recommendations (SSFR) implemented during the 2022/2023 wheat farming season in Ethiopia. The initiative, led by key demand partners such as Digital Green in collaboration with the Ministry of Agriculture (MoA), utilized the advisoryintegrated with the Ethiopian Digital Agro-Climate Advisory Platform (EDACaP), targeting smallholder farmers through various dissemination channels. The collaborative effort, involving MoA,the Ethiopian Institute of Agrocultural Research (EIAR), GIZ-Ethiopia (Supporting Soil Health Inistitives, SSHI), CGIAR EiA (Excellence in Agronomy) Initiative, the Accelerating CGIAR Climate Research in Africa (AICCRA) project, and Digital Green aimed at co-creating tailored agro-advisory content and employing agile dissemination channels. A customized decision support tool (DST) was developed to guide planners, extension workers, and farmers in making optimal planting decisions and fertilizer use. The report details the training of extension agents, using different dissemination channels, primarily using a Telegram bot for communicating the advisory services, and the challenges faced during the pilot, such as fertilizer shortages and limited internet coverage. The findings in August 2023 highlight the effectiveness of the advisory, reaching 50,200 farmers, out of which 8,316 farmers adopting the recommendations. Notably, 20% of adopters were women. The achievement is notable considering the fact that the season was characterized with severe shortage or fertilizer and very high cost. The report also highlights key lessons learned, emphasizing the importance of contextual understanding, collaboration between organizations, and engagement at both the local and ministry levels. The pilot's success underscores the demand for customized advisories and sets the stage for broader adoption and impact within the agricultural extension system.